ANALISIS DAMPAK PENGEMBANGAN KAWASAN INDUSTRI TERHADAP NILAI RUMAH DI SEKITARNY/A (STUDI PADA KAWASAN INDUSTRI CANDI DI KOTA SEMARANG) - , ROFIQ KHAMDANI YUSUF; , Kusdhianto Setiawan, Civilekonom., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research aims to analysethe impact of industrial area development of Candi to residential property value on Sulanji Graha Housing and Pasadena Housing. The tools of analyses were descriptive analyses, compare mean test, and multiple regression analyses with cross sectional data. Dependent variable in this research is residential property value, and independent variabel are land size, building size, age of building, distance to industrial area, distance to main road, and dummy of time. This research was used primary and secondary data. Primary data are taken from direct survey on the location, interview and questioner on Sulanji Graha Housing and Pasadena Housing. The data used in this research are resitential property transaction with sample size are 67 observations. The technic of collecting samples in the field uses purposive sampling technic. The research found that the communities around the industrial area feel more of a negative impact than a positive impacf of industrial area development. The value of losses to be borne is also greater than the value of benefits. The result show us there is a significant different between the residential property value which were transaction before and after the industrial area development. The mean value of houses were transaction after the industria area development is over than its were transaction before. The result from multiple regression analyses shows that only five independent variabels influence significantly to residential property value. Variabel land size, building size, and dummy of time influence significantly positive to residential property value. Variable age of buliding, and distance to main road influence significantly negative to residential property value. Meanwhile, distance to industrial area has positive effect to residential property value but not significant.